Sapiens : a graphic history - Harari, Yuval N.; Vandermeulen, David, 1968-; Casanave, Daniel; Champion, Claire (Colorist); Hunter, Adriana; Harari, Yuval N. (London : Jonathan Cape, 2020)
The first volume of the full-color illustrated adaptation of his groundbreaking book, renowned historian Yuval Harari tells the story of humankind's creation and evolution, exploring the ways in which biology and history have defined us and enhanced our understanding of what it means to be 'human'.
volume one. The birth of humankind.
Graphic novel adaptation of Sapiens: a brief history of humankind by Yuval N. Harari.
Graphic novel adaptation translated from the French, original work in Hebrew.
"First published in Hebrew in 2011 by Kinneret, Zmora-Bitan, Dvir."--Title page verso
"Sapienship Storytelling"--Page 4 of cover
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Civilization -- History -- Comic books, strips, etc; Human beings -- History -- Comic books, strips, etc; World history -- Comic books, strips, etc; Chronology, Historical -- Comic books, strips, etc; Technology and civilization -- History -- Comic books, strips, etc; Agriculture -- History -- Comic books, strips, etc; Comics (Graphic works); Nonfiction comics; Historical comics; Graphic novel adaptations; Comics (Graphic works); Graphic novel adaptations; Graphic novels; Historical comics; History; Nonfiction comics